2018
DOI: 10.1128/jvi.01722-17
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Chimpanzee Adenovirus Vaccine AdC7-M/E Protects against Zika Virus Infection and Testis Damage

Abstract: 38The recent outbreak of Zika virus (ZIKV) has emerged as a global health concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 57 publications
(63 reference statements)
0
47
0
Order By: Relevance
“…Screening of immunogenic peptides which are presented by specific MHC I molecules is crucial for the development of vaccines for infection diseases or cancer immunotherapy and for T-cell immune response evaluation (45)(46)(47)(48)(49)(50)(51). Recently, several pre-clinical and clinical studies have shown that vaccines targeting predicted personal tumor neoantigens are feasibility, safety, and immunogenicity (45,50,(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Screening of immunogenic peptides which are presented by specific MHC I molecules is crucial for the development of vaccines for infection diseases or cancer immunotherapy and for T-cell immune response evaluation (45)(46)(47)(48)(49)(50)(51). Recently, several pre-clinical and clinical studies have shown that vaccines targeting predicted personal tumor neoantigens are feasibility, safety, and immunogenicity (45,50,(52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…The 10.8 kb genome of ZIKV encodes a single polyprotein that, upon action of host and viral proteases, forms three structural proteins (C, PrM, and E) and seven nonstructural proteins (NS1-5 NS2A, NS2B, NS3, NS4A, NS4B, and NS5) (Ye et al, 2016). Numerous approaches are being employed to develop live attenuated virus (Shan et al, 2017), inactivated whole virus (Sumathy et al, 2017), subunit DNA/RNA vaccines (Pardi et al, 2017;To et al, 2018), virus like particles (Espinosa et al, 2018;Salvo et al, 2018), over virus vectored (Xu et al, 2018), and chimeric ZIKV (Kum et al, 2018;Li et al, 2018) vaccines pertaining to several benefits including economical and long-term immunity. But only a few of them have generated appropriate prophylactic responses in tested in vivo models.…”
Section: Chimeric Zika Virusmentioning
confidence: 99%
“…Following humanization, 2A10G6 could be a candidate for immunotherapy. In the second part of his talk, Lianpan presented a chimpanzee adenovirus-based candidate vaccine against ZIKV (Xu et al, 2018). The rationale for using the chimpanzee adenovirus was to take advantage of the low pre-existing immunity against the carrier in the human population (in contrast to human adenovirus).…”
Section: Scientific Sessionsmentioning
confidence: 99%
“…Adenovirus type 7 was engineered to express the ZIKV M and E proteins. A single vaccination elicited potent neutralizing mAbs and achieved sterilizing immunity in mice (Xu et al, 2018). Further assays using a non-human primate model of the disease are planned using this candidate vaccine.…”
Section: Scientific Sessionsmentioning
confidence: 99%